2004
DOI: 10.1094/mpmi.2004.17.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofMsLEC1Transgenes in Alfalfa Plants Causes Symbiotic Abnormalities

Abstract: Legume lectins have been proposed to have important symbiotic roles during Rhizobium-legume symbioses. To test this hypothesis, the symbiotic responses of transgenic alfalfa plants that express a portion of the putative alfalfa lectin gene MsLEC1 or MsLEC2 in either the antisense or sense orientation were analyzed following inoculation with wild-type Sinorhizobium meliloti 1021. MsLEC1-antisense (LEC1AS) plants were stunted, exhibited hypernodulation, and developed not only abnormally large nodules but also nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The pleiotropic effects of MsLEC1 knockdown were either due to off-target activity of the antisense constructs or to MsLEC1 ’s involvement in multiple, essential biochemical pathways. Nevertheless, the reduced expression of MsLEC1 significantly reduced the number of nitrogen-fixing nodules because of premature nodule senescence (Brill et al 2004 ). Southern blot analysis indicated that three copies of a seed-type lectin gene exist in the alfalfa genome (Brill 1997 ), one of which, MsLEC3 , is a pseudogene (W.M.…”
Section: Use Of Model Legumes To Study Lectins and Lectin-like Proteimentioning
confidence: 99%
“…The pleiotropic effects of MsLEC1 knockdown were either due to off-target activity of the antisense constructs or to MsLEC1 ’s involvement in multiple, essential biochemical pathways. Nevertheless, the reduced expression of MsLEC1 significantly reduced the number of nitrogen-fixing nodules because of premature nodule senescence (Brill et al 2004 ). Southern blot analysis indicated that three copies of a seed-type lectin gene exist in the alfalfa genome (Brill 1997 ), one of which, MsLEC3 , is a pseudogene (W.M.…”
Section: Use Of Model Legumes To Study Lectins and Lectin-like Proteimentioning
confidence: 99%
“…One of the proposed functions of legume lectins is to determine the specificity of the rhizobia-legume symbiosis (Hirsh 1999). For this study, Brill et al (2004) obtained transgenic alfalfa plants that expressed the alfalfa lectin MsLEC1 and MsLEC2 in sense and antisense orientations. MsLEC1-antisense (LEC1AS) plants were stunted, exhibited hypernodulation phenotype, and developed not only abnormally large nodules but also numerous small nodules, both of which senesced prematurely.…”
Section: Alfalafa (Medicago Sativa)mentioning
confidence: 99%
“…Special attention should be attributed to lectin receptor kinases and b-galactosidase, which also contain a lectin domain [13,14]. In some plants, for instance, alfalfa, was identified lectin gene MsLEC1 [15]. However, there are no current data on the properties of this protein.…”
mentioning
confidence: 99%
“…The glycoprotein is capable of interacting with the peribacteroid membrane and the nodule bacteria surface [81]. The investigation of the expression of MsLec1, a lectin gene of Medicago sativa, demostrated its relevance for the symbiosis formation [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation